Identifying the Attitudes and Preferences of Parents and Children for Seafood: Summary of Focus Group Results - Anh Sam; Xiang Bi; Lisa House (EDIS)
Seafood contains high-quality protein, vitamins, and minerals that have many health benefits, but the average family’s consumption of seafood in the United States remains below recommended levels. To begin to understand how to raise consumption levels, the study described in this 3-page fact sheet focuses on the influence parents’ seafood consumption habits may have on their children. Written by Anh Sam, Xiang Bi, and Lisa House, and published by the Department of Food and Resource Economics, July 2016.